Effect of Regular Exercise on the Life Satisfaction and Self-Efficacy of the Elderly Obese - Bashan, Ibrahim; Toros, Turhan (Progress in Nutrition, 2022)
This study aimed to investigate whether regular exercise had an effect on the life satisfaction and self-efficacy levels of obese elderly people. The life satisfaction and self-efficacy perceptions of obese individuals aged 65 years and over, who regularly exercised and those that did not exercise were compared using the Satisfaction with Life Scale and the General Self-Efficacy Scale measurement tools. While the mean life satisfaction scores statistically significantly increased among the individuals that exercised regularly, no significant difference was found in relation to the mean self-efficacy scores. The aging world population and increasing age-related obesity continue to be a global problem. In addition to regulating eating habits, which is crucial in preventing obesity, it is necessary to draw attention to the importance of regular exercise, especially in elderly obese individuals.